Ochrona podstawowych praw dziecka w świetle Afrykańskiej Karty Praw i Dobrobytu Dziecka - Diallo, Boubacar Sidi (Studia Edukacyjne, 2018)
The adoption of a binding international treaty on the rights of the child is presented by practitioners and researchers as a “revolution”, marking the transition from the legal status of the child as a subject of the right, to a full actor of rights protection. For the fundamental rights of the child not to remain merely theoretical, but to become concrete and meaningful, it is important to provide them with effective judicial protection. This issue is more than ever topical, with the adoption by the United Nations General Assembly of the Optional Protocol to the Convention on the Rights of the Child establishing a procedure for the submission of communications, which entered into force on 14 April 2014. This new Optional Protocol gives children the right to appeal to the Committee on the Rights of the Child when the rights protected by the Convention and its firsttwo protocols are violated. The purpose of this brief study is to analyze the African Charter on the Rights and Welfare of the Child (African Charter), adopted in 1990, which is the firstregional legal text for children specificallyand as such unique, since no other region in the world has so far developed such a protection mechanism.